Salt tolerance of rice hybrids of the fifth generation - P. I. Kostylev; E. B. Kudashkina (Зерновое хозяйство России)
Soil and water salinization differently affects the growth and development of rice at all stages, reducing its productivity. The article presents the results of the analysis aimed to determine salt resistance of 186 hybrid samples of rice F5 developed in the FSBSI “ARC “Donskoy”. There were studied the samples developed from three hybrid combinations “IR 52713-2B-8-2B-1-2 x Novator”; “IR 74099-3R-3-3 x Novator”; “NSIC Rc 106 x Novator”. The studies were carried out in the ABSIE FSBI HE DonSAU. The rice seeds were germinated in rolls of filter paper on 1.5% NaCl solution and in distilled water. Salt tolerance was determined as the ratio of the percentage of germinated seeds in the experiment to the control. The purpose of the research is to analyze rice samples for salinization resistance. The analysis found out that the rice samples differed significantly among themselves in the length of the sprouts and roots on the salted and control variants. The graphic material of the article reliably shows the relative and absolute values of sprouts and roots in a trial and in a control variant. The analysis showed an average correlation between the length of sprouts in the trial and salt tolerance for sprouts (0.62±0.08), as well as a high correlation between the length of the roots in the trial and salt tolerance for the roots (0.74±0.09). PCR analysis with the help of the markers RM493 and RM7075 made possible to identify in 59 forms the presence of the dominant QTL locus Saltol in the homozygous state. According to the set of indicators 14 best samples were identified. Selected on salt solutions, the best samples with long shoots and roots have been planted on the rice bays of the OS “Proletarskaya” in the form of seedlings.